Optimasi Sistem Informasi Penjadwalan Kuliah Berbasis Heuristic Search yang Dikombinasikan dengan Teknik Smart Back Tracking dan Look Ahead (Studi Kasus pada STMI –Kementerian Perindustrian) - Dedy Trisanto; Muhamad Agus (Politeknik Negeri Padang, 2012)
Scheduling lecture is scheduled number of components consisting of courses, lecturer, students, classrooms, and time with a number of restrictions and requirements (constraints) certain to get optimal results and the best. In this paper will be discussed and created scheduling lecture with a problem-solving approach to the science of Artificial Intelligence (Artificial Intelligence), by using an approximation of the mathematical problem that is aiming to find a situation or object that meets a number of requirements or specific criteria (Constraint Satisfaction Problem) to get the optimal scheduling and the best. To solve these problems the solution search techniques used by an algorithm that will result in optimal scheduling and the best (heuristic search) techniques combined with Smart Backtracking and Look Ahead called Intelligent Search to find and resolve problems when encountered a condition where no there is a solution in due course scheduling constraints and requirements are not met (deadlock). The application of these methods and techniques in the course scheduling information system is built, using the PHP programming language and MySQL database to solve the problem of scheduling to get optimal results and the best.